Rotation & differential rotation of the active Kepler stars. Issue Volume 9:Issue S302(2013) (7th August 2014) - Reinhold, Timo; Reiners, Ansgar; Basri, Gibor
Abstract: Stellar rotation is a well-known quantity for tens of thousands of stars. In contrast, differential rotation (DR) is only known for a handful of stars because DR cannot be measured directly. We present rotation periods for more than 24, 000 active stars in the Kepler field. Thereof, more than 18, 000 stars show a second period, which we attribute to surface differential rotation. Our rotation periods are consistent with previous measurements and the theory of magnetic braking. Our results on DR paint a rather different picture: The temperature dependence of the absolute shear δΩ is split into two groups separated around 6000 K. For the cooler stars δΩ only slightly increases with temperature, whereas stars hotter than 6000 K show large scatter. This is the first time that DR has been measured for such a large number of stars.